Revisiting K.A.C. Creswell’s Theory on the First Mosque in Islam - Ayyad, Essam S. (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2017)
Professor Keppel Archibald Cameron Creswell (1879â€“1974), better known as K.A.C. Creswell or simply Creswell, was definitely one of the most prominent and prolific scholars in the field of Islamic art and architecture. His gigantic two-volume Early Muslim Architecture, of which Volume I was first published in Oxford in 1932, remains widely acknowledged as the most important reference for early Islamic architecture so far. Nevertheless, Creswellâ€™s hypothesis on the genesis of the mosque type and his perception of the first mosque in Islam betray a considerable amount of dubiety and suffer a myriad of critical deficiencies. As he maintains, the making of the mosque, as defined in the modern sense, was launched not by the Prophet, as commonly believed, but by ZiyÄd b. AbÄ«h when he reconstructed the mosque of Baá¹£ra in 45/665. Astonishingly, these views of Creswell were adopted and further enhanced by quite a number of notable specialists over eighty-five years. This article will subject such views to scrutiny with the aim of identifying the first mosque in Islam and the religious as well as historical contexts in which it emerged. This discussion becomes more persistent, however, given the dominant misconceptions about the topic in Western as well as Muslim scholarships.